Estimation of remaining dentine thickness below deep lesions of caries - Lancaster, P. E.; Craddock, H. L.; Carmichael, F. A. (British dental journal, 2011)
Key Points Stepwise excavation is an accepted technique for restoring deep caries lesions. The remaining dentine thickness influences pulp vitality and the outcome of certain restorative procedures. Reliable measurement of tooth dimensions from an intra-oral conventional or digital radiograph was not achievable. The general trend for the radiographic images was to over-estimate the remaining dentine thickness. Objective The objective of this study was to investigate agreement between the estimated remaining dentine thickness (RDT) under lesions of caries, measured from a conventional in vivo periapical radiograph, compared directly to the measured RDT of the tooth. Additional investigation was to be made for agreement between in vitro digital radiographs and conventional radiographs. Design and setting This was a cross-sectional, single centre study at Leeds Dental Institute, United Kingdom, in 2009. Subjects, materials and methods Twenty-five carious teeth with occlusal or proximal lesions were collected from patients aged 19 to 82 years attending the Oral Surgery Department. Each patient had a pre-extraction in vivo periapical radiograph of the tooth demonstrating an intact layer of dentine below the lesions of caries. Post-extraction in vitro digital and conventional radiographs were taken. Main outcome measures Agreement of the RDT was analysed using Bland-Altman plots. Results A trend for the radiographic images to over-estimate the RDT compared to the tooth was found. Greater over-estimation of the RDT by conventional radiographs both in vivo and in vitro was shown compared to the in vitro digital images in the majority of cases. Conclusion This analysis has demonstrated it is not possible to estimate the dimension of the RDT from a periapical radiograph.